PENGEMBANGAN MEDIA KOTAK MEMBACA CERDAS PADA PEMBELAJARAN MEMBACA PERMULAAN DI KELAS 1 SDN BILAPORAH 1 BANGKALAN - Hasanah, Alfiatul; Fauziah, Humairah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research and development study aims to develop the Kotak Membaca Cerdas (Smart Reading Box) product for early reading instruction in Grade I at SDN Bilaporah 1 Bangkalan, ensuring that the product is valid, effective, and appealing. This study employed the ADDIE development model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this research were Grade I students at UPTD SD Negeri Bilaporah 1 Bangkalan. The validation results from the learning media expert showed a percentage of 94%, categorized as very valid. Validation from the language and material expert obtained a percentage of 88%, categorized as very valid, while validation from the instructional design expert obtained a percentage of 93%, also categorized as very valid. The effectiveness of the media was demonstrated by an average student activity score of 96%, categorized as effective and suitable for use. In addition, student learning outcomes analyzed using the classical completeness formula showed a completeness rate of 100%. The attractiveness of the media was measured through a student response questionnaire, which obtained a score of 99%, categorized as very attractive. Based on these results, the Kotak Membaca Cerdas learning media is declared very valid, effective, and attractive for use in early reading instruction for Grade I elementary school students.